PENGARUH PERSEPSI MASYARAKAT PADA KINERJA KEPOLISIAN TERHADAP KEPERCAYAAN PADA KEPOLISIAN - Lina Febrianti; Herdiyan Maulana (Journal of Research and Measurement in Psychology, 2013)
This study aims to look at the effect on the public perception of trust in the police. The research was conducted in December 2012. The design of this this study is a quantitative method. Subjects in this research were 124 citizen in the Jabodetabek area with an age range of 18 years and minimum of High School education/equivalent. It’s using the incidental technique sampling to get the sample. Data of this research was collected by the instrument which has 27 aitem perception and trust instrument which has 37 items. These results show that there is a significant effect between perceptions of trust in the police. Perceptions positive effect on confidence. So Ho is rejected and Ha accepted perceptions of the effective contribution of 37.5% confidence.